"A Thousand Petty Troubles": Margaret Hale's Emotional Labour in North and South. Issue 4 (1st October 2020) - Schroeder, Janice
ABSTRACT: This article examines Margaret Hale's unpaid emotional labour in Elizabeth Gaskell's North and South (1854). Emotional labour, a term coined in 1983 by sociologist Arlie Russell Hochschild, rebrands Victorian keywords such as sympathy, duty, and woman's mission . The application of the term emotional labour to Gaskell's novel draws attention to the laborious nature of daily practices of household sympathy. Margaret's emotional management of the Hale and Higgins households shapes both plot and character; concealing her own emotions in order to generate appropriate feelings in others is a form of work that is both alienating and productive of middle-class domestic competence. The article also examines the clash between Gaskell and Charles Dickens over North and South 's serialization in Household Words . Their disagreement about the novel's division into chapters reveals how emotional labour is enfolded not only in the novel's plot but also in its form. The appearance of chapter divisions as "natural" and inconspicuous interruptions to both Margaret's and readers' time and attention demonstrates the emotional work that chapters perform for both character and audience.